2016
DOI: 10.2500/ajra.2016.30.4297
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis: Epidemiology and Burden of Disease

Abstract: CRS is a common disease with a large and vast symptom burden with high indirect costs. Although clinicians are focused by guidelines on sinus-specific symptoms, patients seem to be most impacted by the general-health-related consequences of CRS. An expanded understanding of the extent and costs of these symptoms will allow for a cost-effective allocation of limited health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
233
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 275 publications
(260 citation statements)
references
References 54 publications
3
233
1
6
Order By: Relevance
“…In clinical use for asthma or other chronic diseases, the concept of control is often applied to the most significant disease manifestations, which can be identified as those that have the greatest impact on QOL. It is well described that CRS is associated with a significant general health‐related QOL detriment that is comparable to the QOL detriment caused by severe asthma . Studies that have sought to dissect the major contributors that are associated with decreased general health‐related QOL in CRS have found that chronic sinonasal symptomatology has the greatest impact on general health‐related QOL .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical use for asthma or other chronic diseases, the concept of control is often applied to the most significant disease manifestations, which can be identified as those that have the greatest impact on QOL. It is well described that CRS is associated with a significant general health‐related QOL detriment that is comparable to the QOL detriment caused by severe asthma . Studies that have sought to dissect the major contributors that are associated with decreased general health‐related QOL in CRS have found that chronic sinonasal symptomatology has the greatest impact on general health‐related QOL .…”
Section: Discussionmentioning
confidence: 99%
“…CRS is commonly classified by the presence or absence of nasal polyps on endoscopy or imaging as recommended by recent AAO-HNS guidelines [1]. CRS is widespread with a reported prevalence of 4.5–12% in the general population, and the subset of patients with nasal polyposis observed in population-based studies ranges from 0.5–4.3% with the higher prevalence observed in Western countries, male patients, the elderly, and asthmatics [2] [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is one of the most common causes of olfactory dysfunction in the general population, impacting 5% to 15% of adults worldwide . Impaired olfaction is one of the cardinal symptoms of CRS and can be found in 30% to 78.2% of patients, varying somewhat by age, gender, and presence of polyps .…”
mentioning
confidence: 99%